Bone marrow hypoplasia: atypical manifestation of hyperthyroidism - Lucia, Carolina Vitória de (2021)
Hematological changes such as anemia or pancytopenia can occur as atypical manifestations of hyperthyroidism. Although most cases of pancytopenia in Graves’ disease are due to the use of antithyroid drugs (thionamides), it can also be associated with untreated hyperthyroidism, thus manifesting as a serious complication. This study aims to report the case of a 39-year-old hyperthyroid female patient who developed pancytopenia during hospitalization. Data were collected by means of the medical record, an interview conducted with the patient, and literature review. The patient was admitted to a hospital in Salvador presenting lower extremity edema that progressively evolved to anasarca within 45 days prior to the interview. She also presented weight loss, paroxysmal nocturnal dyspnea, tachycardia, sweating, chills, and laboratory test results for pancytopenia. The case reported here demonstrates an atypical and rare manifestation of hyperthyroidism that improved after the beginning of the treatment, reaching the euthyroid state.